The Complete Mitochondrial Genome of Ugyops sp. (Hemiptera: Delphacidae) - Yu, Fang (J Insect Sci, 2018)
The complete mitochondrial genome (mitogenome) of Ugyops sp. (Hemiptera: Delphacidae) was sequenced, making it the first determined mitogenome from the subfamily Asiracinae, the basal clade of the family Delphacidae. The mitogenome was 15,259 bp in length with A + T content of 77.65% and contained 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and a control region. The gene order was identical with that of the ancestral insect. The nucleotide composition analysis indicated that the whole mitogenome was strongly A-skewed (0.288) and highly C-skewed (−0.270). For PCGs on the J-strand, the AT skew was positive, and the GC skew was negative. All PCGs started with canonical ATN codons, except for cox1 and nad5, which used CTG and GTG as start codon, respectively. All tRNAs could fold into typical cloverleaf secondary structures, with the exception of trnS1 (AGN), in which the dihydrouridine arm was reduced to a simple loop. The control region included a poly-T stretch downstream of the small rRNA gene (rrnS), a subregion of higher A + T content and tandemly repeated sequence near trnI. The mitogenome of Ugyops sp. could be very helpful in exploring the diversity and evolution of mitogenomes in Delphacidae.